Mental Toughness: A Gender-Based Descriptive Study of Pencak Silat Athletes on the West Java XV PORPROV Team of Subang Regency - Wahyu Saputra; Asep Akbaruddin (Jurnal Master Penjas & Olahraga, 2026)
This study aimed to describe the level of mental toughness among pencak silat athletes on the West Java XV PORPROV team of Subang Regency. The study employed a descriptive quantitative approach using a survey method. The participants were 15 athletes, and instrument used was a 23-item mental toughness questionnaire covering four components: thrive through challenge, sport awareness, tough attitude, and desire success. The results showed that the athletes’ overall mental toughness score had a mean of 67.00 with a standard deviation of 8.86, a minimum score of 56, and a maximum score of 81. Based on the mean ± 1 SD categorization, 2 athletes (13.3%) were in the low category, 9 athletes (60.0%) were in the moderate category, and 4 athletes (26.7%) were in the high category. Overall, mental toughness of the pencak silat athletes on the West Java XV PORPROV team of Subang Regency was in the moderate category.